Physician and patient satisfaction with the switch to remote outpatient encounters in epilepsy clinics during the Covid-19 pandemic. (October 2021) - Teng, T.; Sareidaki, D.E.; Chemaly, N.; Bar, C.; Coste-Zeitoun, D.; Kuchenbuch, M.; Nabbout, R.
Abstract: Purpose: Analyzing parents' and physicians' opinions regarding phone-based encounters in emergency shifts of a French pediatric epilepsy center compared to traditional face-to-face encounters during the first lockdown of the COVID-19 pandemic Methods: Prospective monocentric study on remote encounters at Necker rare epilepsy reference center from March 20th, 2020 to April 23rd, 2020 due to lockdown measures. This study was conducted with a survey based on 5-point Likert scales (LS-2/2 ) designed for both parents and physicians. We compared first versus follow-up encounters as well as physicians' and parents' opinions. Results: We had a total of 224 responses, among which 204 were completed by physicians (91%) and 173 (84, 4%) by parents. Twenty five were first encounters (14, 2%). Physicians pointed out the need for clinical examination (42.6%), mainly for first encounters (p=0.0004). Physicians rated the quality of communication lower (p=0.003) as their capacity to answer parents' questions (p=0.004). They were significantly less satisfied with remote encounters compared to parents (p<10 −4 ). We identified six urgent (2.9%) and 50 semi-urgent (24%) situations requiring programming face-to-face encounter during or shortly after the lockdown. Conclusion: Remote encounters could be a helpful practice for pediatric patients with epilepsy in emergency situations such as pandemics. It allowed the identification and prioritization of emergency situations. Physicians were less positive than parents. We raised the possible use of remote encounters in association to face-to-face encounters for routine follow-up of pediatric patients with epilepsy.